Integrated metabolomic insights into the mechanism of Bacillus coagulans in enhancing intestinal recovery following gynecological laparoscopic surgery: a randomized clinical trial - Xu, Juan; Dong, Lingjun; Feng, Chunqi; Guan, Zhaobo; Zhang, Jingmin; Bai, Niuniu; Niu, Zhanqin; Chen, Weihong; Gao, Weiqi (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the efficacy and mechanistic underpinnings of live Bacillus coagulans tablets in accelerating recovery of intestinal function after gynecologic laparoscopic surgery.MethodsA randomized, double-blind, placebo-controlled trial included 115 patients undergoing gynecological laparoscopy, assigned to placebo control (PC, n = 39), conventional dose (CD, n = 38), and high dose (HD, n = 38) groups. Clinical recovery was assessed by timing of first postoperative bowel movement and gastrointestinal adverse reactions. Plasma levels of motilin (MTL) and serotonin (5-HT) were measured using ELISA. Plasma metabolite profiles were analyzed via metabolomics to elucidate treatment-related metabolic pathways.ResultsTreatment groups (CD and HD) exhibited significantly reduced time to first postoperative defecation and fewer gastrointestinal adverse reactions compared to PC (P < 0.05), without significant differences between CD and HD groups. Plasma MTL and 5-HT levels significantly increased postoperatively in the treatment groups compared with PC (P < 0.05), without dose-dependent differences. Metabolomics identified 50 and 73 differential metabolites in CD and HD groups post-treatment, respectively, enriched mainly in pathways involving tryptophan, tyrosine, histidine, kynurenine, primary bile acids, and short-chain fatty acids.ConclusionLive Bacillus coagulans tablets effectively promoted postoperative intestinal recovery in patients undergoing gynecological laparoscopy. The mechanisms likely involve enhanced secretion of MTL and 5-HT, coupled with regulation of key metabolic pathways including tryptophan, tyrosine, kynurenine, histidine metabolism, primary bile acid synthesis, and SCFA metabolism. This study provides insights into probiotics’ potential to improve postoperative gastrointestinal outcomes.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400079659.